Neo-Ahl Al-Hadîts In Contemporary Islamic Legal Thought: The Influence of Nâshir al-Dîn al-Albânî in the Salafist Movement in Indonesia - Faizin, Afwan (Madania: Jurnal Kajian Keislaman, 2023)
Nâshîr al-Dîn al-Albânî is one of the most influential figure in the contemporary Salafist movement, alongside Bin Bâz and Uthaymin. This article will discuss the influence of Nasir al-Din al-Albâni on Indonesian Salafi Islamic legal thought. In the discourse of Islamic legal thought in Indonesia, some scholars explain the importance of al-Albânî's role in defending Ibn Bâz's fatwas by writing dozens of works, including his fatwas, that have been translated into Indonesian. On the other hand, other scholars emphasized al-Albânî's central role in the global Salafist movement as a contemporary Salafist ideologue. This figure calls for ijtihad based on authentic traditions and rejects tackled and bequeaths his brand of Salafism in deconstructing the traditions of schools of fiqh. The research question is what is the influence of al-Albânî's takhrîj traditions on Indonesian Salafist Islamic legal thought? This is qualitative research with a historical, hadith scientific, and sociological approach. The findings of this study are that the traditions of takhrîj al-Albânî and its understanding have led to the strengthening of a strict literal way of Islamic law. Al-Albâni greatly influenced Indonesian Salafists in forming a pattern of thought called "Neo-Ahl al-Hadîts". The Neo-Ahl al-Hadîts legal thought inflicts radical and intolerant attitudes among Indonesian Salafist. Nâshir al-Dîn al-Albânî adalah salah satu tokoh paling berpengaruh dalam gerakan Salafi kontemporer, bersama Bin Bâz dan Uthaymin. Artikel ini akan membahas pengaruh Nâshir al-Dîn al-Albânî dalam pemikiran hukum Islam Salafi Indonesia. Dalam wacana pemikiran hukum Islam di Indonesia, beberapa ulama menjelaskan pentingnya peran al-Albânî dalam membela fatwa-fatwa Ibnu Bâz dengan menulis puluhan karya, termasuk fatwanya, yang telah diterjemahkan ke dalam bahasa Indonesia. Di sisi lain, ulama lain menekankan peran sentral al-Albânî dalam gerakan Salafi global sebagai ideolog Salafi kontemporer. Tokoh ini menyerukan ijtihad berdasarkan hadis shahih dan menolak menegur dan mewariskan merek Salafismenya dalam mendekonstruksi tradisi mazhab fikih. Pertanyaan penelitiannya adalah bagaimana pengaruh tradisi takhrîj al-Albânî terhadap pemikiran hukum Islam Salafi Indonesia? Jenis penelitian ini adalah kualitatif dengan pendekatan sejarah, ilmu hadis, dan pendekatan sosiologis. Temuan penelitian ini adalah bahwa hadis takhrîj al-Albânî dan pemahamannya telah menyebabkan penguatan hukum Islam secara literal yang sangat kaku. Al-Albâni sangat mempengaruhi kaum Salafi Indonesia dalam membentuk pola pemikiran yang disebut “Neo-Ahl al-Hadîts”. Kemudian, pemikiran hukum Neo-ahl al-Hadîts melahirkan sikap radikal dan intoleran di kalangan Salafi Indonesia.